2012
DOI: 10.1103/physreva.85.023428
|View full text |Cite
|
Sign up to set email alerts
|

Ionization in elliptically polarized pulses: Multielectron polarization effects and asymmetry of photoelectron momentum distributions

Abstract: In the tunneling regime we present a semiclassical model of above-threshold ionization with inclusion of the Stark shift of the initial state, the Coulomb potential, and a polarization induced dipole potential. The model is used for the investigation of the photoelectron momentum distributions in close to circularly polarized light, and it is validated by comparison with ab initio results and experiments. The momentum distributions are shown to be highly sensitive to the tunneling exit point, the Coulomb force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
122
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(130 citation statements)
references
References 78 publications
8
122
0
Order By: Relevance
“…Our approach is simpler and has been used in Refs. [36,37,39,40,44]. Our approach would likely overestimate the core polarization at small r. Nevertheless, we will show below that our numerical results using the SAE picture are in good agreement with their data and with experiments [25].…”
Section: A Numerical Solution Of the Time-dependent Schrödinger Equasupporting
confidence: 70%
See 3 more Smart Citations
“…Our approach is simpler and has been used in Refs. [36,37,39,40,44]. Our approach would likely overestimate the core polarization at small r. Nevertheless, we will show below that our numerical results using the SAE picture are in good agreement with their data and with experiments [25].…”
Section: A Numerical Solution Of the Time-dependent Schrödinger Equasupporting
confidence: 70%
“…[34,35]. Note that the effect of the dynamic core polarization was considered earlier in the context of the photoelectron momentum distribution [36]. It was also found that accounting for this effect is important for the correct reading of the attoclock experiments by Pfeiffer et al [37], even for argon.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Specifically, we do not include the time-dependent modulation of the ionization rates induced by the oscillation of the remaining bound wave function caused by the removal of the first electron [19,21,22]. Additionally, we neglect forces between the two electrons and ions as well as between electrons [23][24][25]. However, the model reproduces the main features observed experimentally and yields a great deal of insight into the underlying dynamics.…”
Section: Semiclassical Model Of Sequential Double Ionizationmentioning
confidence: 98%